Subfossil Records of the Arctic Fox (Alopex Lagopus) Compared to Its Present Distribution in Norway - Frafjord, Karl; Hufthammer, Anne Karin (ARCTIC, 1994)
We studied the prehistoric and historic distribution of arctic foxes in Norway by examining material and reports from archaeological excavations. A total of 44 arctic fox bones were found in 15 excavations, all of which were younger than 5000 years before present (B.P.). The majority of these sites was located within or close to the present distribution of arctic foxes. Additionally, 44 naturally deposited arctic fox bones were found in two excavations dated 36 000-28 000 and 13 000 B.P. respectively, indicating that the arctic fox also lived along the Norwegian coast in the Pleistocene. No arctic fox bone was dated to the period 9000-5000 B.P., and the species may have been rare or absent during this comparatively warm period. Since most bones (61%) were from the distal part of the limbs, the foxes may have been skinned elsewhere and transported to the site of deposition. Bones from red foxes were found in three excavations within the present distribution of arctic foxes, indicating that the arctic fox was relatively more abundant than red foxes during the late prehistoric and the historic periods in south Norway, but less abundant in north Norway.Key words: arctic fox, red fox, prehistoric and historic distributions, archaeological excavations, Norway On a étudié les distributions préhistorique et historique du renard arctique en Norvège, en examinant du matériel et des rapports provenant de fouilles archéologiques. Au total, 44 os de renard arctique ont été trouvés dans des fouilles effectuées sur 15 sites, et tous les os dataient de moins de 5000 ans avant le présent. La majorité de ces emplacements était située à l'intérieur ou près de la distribution actuelle du renard arctique. On a en outre trouvé 44 os de renard arctique déposés naturellement dans deux fouilles datées respectivement de 36 000 à 28 000 ans avant le présent et de 13 000 ans avant le présent, ce qui révèle que le renard arctique vivait aussi le long du rivage norvégien au cours du pléistocène. Aucun os de renard arctique n'a été daté de ...